Pregabalin Exerts Oppositional Effects on Different Inhibitory Circuits in Human Motor Cortex: A Double‐blind, Placebo‐controlled Transcranial Magnetic Stimulation Study - Lang, Nicolas; Sueske, Elke; Hasan, Alkomiet; Paulus, Walter; Tergau, Frithjof (Epilepsia (Copenhagen), 2006)
Purpose: To explore acute effects of pregabalin (PGB) on human motor cortex excitability with transcranial magnetic stimulation (TMS). Methods: PGB, 600 mg/day, was orally administered in 19 healthy subjects twice daily in a randomized, double‐blind, placebo‐controlled crossover design. Several measures of motor cortex excitability were tested with single‐ and paired‐pulse TMS. Results: Mean short‐interval intracortical inhibition (SICI) was reduced after PGB (74 ± 7% of unconditioned response) compared with placebo (60 ± 6% of unconditioned response). In contrast, mean long‐interval intracortical inhibition (LICI) was increased by PGB (26 ± 4% of unconditioned response) compared with placebo (45 ± 8% of unconditioned response), and mean cortical silent period (CSP) showed an increase from 139 ± 8 ms or 145 ± 8 ms after placebo to 162 ± 7 ms or 161 ± 10 ms after PGB. Motor thresholds, intracortical facilitation, and corticospinal excitability were unaffected. Conclusions: The observed excitability changes with oppositional effects on SICI and LICI or CSP suggest γ‐aminobutyric acid (GABA)B‐receptor activation. They are markedly distinct from those induced by gabapentin, although both PGB and gabapentin are thought to mediate their function by binding to the α(2)‐δ subunit of voltage‐gated calcium channels. Conversely, the TMS profile of PGB shows striking similarities with the pattern evoked by the GABA‐reuptake inhibitor tiagabine.